2014
DOI: 10.1186/s12930-014-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural and socioeconomic variations in lifetime prevalence of symptoms of sexually transmitted infections among Bangladeshi adolescents

Abstract: Aim: To identify socioeconomic and urban-rural variations in self-reported lifetime prevalence of symptoms of sexually transmitted infections (STI). Methods: This cross-sectional study used data from the Bangladesh Adolescents Survey 2005 conducted on 11,986 adolescents, using a cluster sampling methods. Data were analysed using SPSS applying principle components analysis, multivariate logistic regression analysis, and prevalence ratio (PR) with 95% confidence interval (CI).Results: Self-reported lifetime prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…The observed associations of STI symptoms with demographic, socioeconomic, and behavioral risk factors moderately concur with previous studies. The studies demonstrated increased STI symptoms among women aged 25-34 years [16,24], those with limited decision-making capacity regarding healthcare [17], those with lower levels of education [22], and women who used contraceptives such as condoms and oral pills [18]. Thus, the current study's findings contribute to a growing body of literature [9,16,18,19,22,24,27,28] that has documented the association of STI symptoms with varied demographic, socioeconomic, and behavioral risk factors.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The observed associations of STI symptoms with demographic, socioeconomic, and behavioral risk factors moderately concur with previous studies. The studies demonstrated increased STI symptoms among women aged 25-34 years [16,24], those with limited decision-making capacity regarding healthcare [17], those with lower levels of education [22], and women who used contraceptives such as condoms and oral pills [18]. Thus, the current study's findings contribute to a growing body of literature [9,16,18,19,22,24,27,28] that has documented the association of STI symptoms with varied demographic, socioeconomic, and behavioral risk factors.…”
Section: Discussionsupporting
confidence: 51%
“…Explanatory variables were categorized into demographic, socioeconomic, and behavioral factors (Table 1). The choice of these variables and categorization were based on the extensive review of existing Bangladeshi and international studies [18,22,24,[27][28][29][30][31][32]. Demographic factors included in the study were participants' age (15-24, 25-34, 35-49 years), age at first marriage (9-14 years, 15-17 years, ≥18 years), and residence type (urban, rural).…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Sebuah studi di Bangladesh tahun 2015 menemukan bahwa kejadian IMS lebih banyak ditemukan pada responden di pedesaan (11,9%) dibandingkan di perkotaan (3,4%). 13 Aksesibilitas menjadi hal penting jika menyangkut pencarian pelayanan kesehatan, jarang ditemukannya pelayanan kesehatan di pedesaan akan membuat seseorang kesulitan untuk mengakses ataupun mencari informasi tentang IMS sehingga dapat memicu pertumbuhan kasus IMS. 14 Wanita merupakan kelompok yang sangat rentan terhadap IMS, terutama usia remaja (15-24 tahun).…”
Section: Pendahulianunclassified